Late Presentation of Right-sided Bochdalek Hernia - Case Report and Literature Review - Vacić, Nikola; Kostić, Ana; Đorđević, Ivona; Jovanović, Andrijana; Stanković, Radomir (Medical Word, 2026)
Congenital diaphragmatic hernia is a congenital anomaly characterized by a defect in the diaphragm, allowing abdominal organs to herniate into the thoracic cavity. It is most commonly diagnosed during the neonatal period; however, cases diagnosed beyond this period have also been described. We present the case of a 14-month-old male child referred from a regional healthcare center to our institution due to marked irritability during the day, gastrointestinal symptoms, and abnormal findings on the plain chest and abdomen radiographies, which raised suspicion of congenital diaphragmatic hernia. The main gastrointestinal symptom was vomiting, with a normal stool pattern and no presence of blood. Upon admission, multislice computed tomography (MSCT) of the chest and abdomen confirmed herniation of abdominal contents into the right hemithorax, consistent with a right-sided Bochdalek hernia. Exploration of the abdominal cavity was performed through a right subcostal laparotomy. Loops of the small intestine were observed herniating through a posterolateral defect of the right hemidiaphragm into the right thoracic cavity. Careful reduction of the small intestine into the abdominal cavity was followed by medial and cranial mobilization of the liver, which allowed for clear visualisation of the diaphragmatic defect. The defect was repaired using interrupted sutures. The postoperative course was uneventful, and the patient was discharged home on the seventh postoperative day. Although late-presenting congenital diaphragmatic hernia generally has a favourable prognosis, it should not be regarded as a benign condition. This entity should always be considered in the differential diagnosis of patients with respiratory and/or gastrointestinal symptoms unresponsive to standard therapy, especially when abnormalities are noted on plain chest radiography.